Answer :
Answer:
4
Step-by-step explanation:
Solve for x:
-log(8)/log(x) = -3/2
Take the reciprocal of both sides:
-log(x)/log(8) = -2/3
Multiply both sides by -log(8):
log(x) = (2 log(8))/3
(2 log(8))/3 = log(8^(2/3)) = log(4):
log(x) = log(4)
Cancel logarithms by taking exp of both sides:
Answer: x = 4
Answer:
B. 4
Step-by-step explanation:
If Logx (1 / 8) = - 3 / 2, then x is equal to
Solution
Rewrite the logarithmic equations using exponential equation
x- 3 / 2 = 1 / 8
The above equation may be rewritten as
x - 3 / 2 = 1 / 23 = 2-3
(√x)-3 = 2-3
The above equation gives
√x = 2 or x = 4